Low stress abrasion-corrosion of high-Cr white cast iron: Combined effects of particle angularity and chloride ions - Salasi, Mobin; Iannuzzi, Mariano; Rickard, William; Quadir, Z. (2019)
Tribo-electrochemical behavior of a high chromium white cast iron (high-Cr WCI) used in, e.g., slurry pumps in mining and mineral processing applications, was investigated using a combination of electrochemical techniques, including zero resistance amperometry as well as potentiostatic and potentiodynamic polarisation. The effects of third body particles angularity on the localised tribocorrosion response of the cast alloy was studied during and post abrasion-corrosion by round ceramic beads and semi-angular silica sand particles. Advanced characterization methods such as electron backscatter diffraction and focused-ion beam cross-sectioning of affected areas were also employed to understand the wear and corrosion interactive actions. It was found that in chloride-free solutions, the behavior of high-Cr WCI resembled that of the austenitic 316 SS studied before. In contrast, in chloride-containing electrolytes, the semi-angular silica sand particles increased interfacial (carbide/matrix) localised corrosion susceptibility during and post-abrasion as indicated by the stark increase in anodic current and the morphology of the attack. Semi-angular silica sand abrasives had a greater adverse impact on post-abrasion interfacial corrosion vulnerability, compared to round ceramic beads. The complex behavior observed indicates that any material developed for tribocorrosive conditions must account for the particles angularity and their subsequent effects on localised corrosion.